Geochemistry of a Triassic dyke swarm in the North Patagonian Massif, Argentina : Implications for a postorogenic event of the Permian Gondwanide orogeny - González, Santiago Nicolás (2016)
Permo-Triassic magmatism is widespread in the eastern North Patagonian Massif and has been related tothe Gondwanide orogeny. Although a magmatic arc setting is widely accepted for the Permian plutonicrocks, the origin and geotectonic setting for the Triassic plutonic and volcanic rocks are still unknown. ANW-SE Triassic dyke swarm composed of andesites and latites with minor rhyolites was previouslydescribed in the Sierra GrandeeRincon de Paileman area. The dyke swarm was associated withextensional tectonics which was linked to a postorogenic process.In this paper we present new geochemical data of the rocks that form the swarm. Trachyandesites andrhyolites were separated based on their geochemical characteristics. Both groups may be consideredoriginated from different sources. On the other hand, the content of incompatible elements (LILE andHFSE) indicates a strong relation between the swarm and an active continental margin. The samples alsoshow a transitional signature between continental-arc and postcollisional or anorogenic settings.The new geochemical data on the dyke swarm support the idea of a magmatism that was linked to apostorogenic extensional tectonic regime related to a continental magmatic arc. Such an extensionstarted in the Paleopacific margin of Pangea during the Anisian and might indicate the beginning of thePangea break-up.